A Cultural-Historical Activity Theory Investigation of Contradictions in Open and Distance Higher Education among Alienated Adult Learners in Korea National Open University - Joo, K. P. (International Review of Research in Open and Distributed Learning, 2014)
Drawing upon cultural-historical activity theory, this research analyzed the structural contradictions existing in a variety of educational activities among a group of alienated adult students in Korea National Open University (KNOU). Despite KNOU’s quantitative development in student enrollment, the contradictions shed light on how the institution’s top-down, bureaucratic pedagogical system collided with individual expectations and needs. In particular, the participants’ critical viewpoints demonstrate the incompatible social roles that the open and distance higher education institution plays in Korean society. For example, while KNOU contributes to extending higher education opportunities for those who have unmet educational needs, the value of the KNOU degree has not been socially acknowledged since there is little, if any, competition in the entrance process. This study also documents how these contradictions were culturally and historically embedded in the participants’ distance higher education activities. Given the persistent contradictions, the research findings illuminate that KNOU’s efficiency-oriented model has not effectively facilitated the students’ learning as its distance higher education system is inevitably based on a compromise between a competitive, quality curriculum and the efficient extension of audiences.